Features of institutional autonomy of the Kazakhstan’s universities - Nurgaliyeva, Saniya; Zeynolla, Saule; Tulenova, Ulday; Zulkarnayeva, Zhamila; Yespolova, Gulden; Saule, Zeinolla (Opción, 2019)
The article purpose is to study the development of institutional autonomy of Kazakhstan’s higher education institutions. The methods of the comparative analysis, system and logical analysis, the method of information synthesis are used during this research. The research results show that the difference between an ideal form of autonomy of Kazakhstan’s universities and real autonomy of the higher educational institutions is indistinct. There is no clear consensus about what level of financial and academic autonomy is desirable. Roles of key components in the field of the academic management are not clearly determined yet.